FUNGAL DISEASES - O'tayeva Sitora Malik qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article provides information on the most effective and inexpensive remedies for the prevention of fungal diseases that are currently common in humans.